Reconsideration of Local Government at Village Level: A Legal Study - Hasina, Nusrat; Hasan, Gazi Saiful (Global Disclosure of Economics and Business, 2015)
Establishing a local government institution in appropriate tire can easily help to get the utmost benefit of decentralization in Bangladesh. In this paper, village has been identified as an important tier to fulfill the objectives. Analysis of the historical development of local government in Bangladesh has been taken into concern to prove the fact. This paper especially focuses as well recommends establishing local government at village level which is the lowest tier of administrative decentralization in Bangladesh. Village government can also be the best tier to practice local level democracy and can ensure effective participation in decision making and also in implementing other activities related to villagers.